Given differential equation is, "\\frac{dx}{x^2-y^2-z^2}=\\frac{dy}{2xy}=\\frac{dz}{2xz}"
Taking last two terms, "\\frac{dy}{2xy}=\\frac{dz}{2xz} \\implies \\frac{dy}{y}=\\frac{dz}{z}"
Integrating both sides, we get,
"y=cz" (1)
Taking first and last term,
"\\frac{dx}{x^2-y^2-z^2}=\\frac{dz}{2xz}"
"\\frac{dx}{x^2-c^2z^2-z^2}=\\frac{dz}{2xz}"
"\\frac{dx}{dz} = \\frac{x^2-z^2(1+c^2)}{2xz}"
Putting x=vz, then, "\\frac{dx}{dz} = v+z\\frac{dv}{dz}"
Then equation will be, "v+z\\frac{dv}{dz} = \\frac{v^2x^2-z^2(1+c^2)}{2vz^2} = \\frac{v^2-(1+c^2)}{2v}"
"z\\frac{dv}{dz} = -\\frac{v^2+(1+c^2)}{2v}"
"\\frac{2vdv}{v^2+(1+c^2)} = -\\frac{dz}{z}"
Integrating the above equation, "log|v^2+(1+c^2)|=-log|z|+log|c_1| \\implies v^2+(1+c^2)=\\frac{c_1}{z}"
Putting value of v, "\\frac{x^2}{z^2}= \\frac{c_1}{z} -(1+c^2)"
"x^2 = c_1z - z^2(1+c^2)"
Solving quadratic equation for z, we get,
"z=\\frac{c_1\\pm \\sqrt{(c_1^2-4x^2(1+c^2)})}{ 2(1+c^2)}" (2)
Equation (1) & (2) are solutions.
Comments
Leave a comment